Developing critical thinking competence in algebraic thinking using augmented reality for junior high school (PRISMA, Prosiding Seminar Nasional Matematika, 2020)
The algebra learning promotes thinking about recognition and analysis of pattern, reasoning and problem solving skills, and generalizing arithmetic operation through representation with symbols. And all of these aspects need critical thinking competence. However, the high level of abstraction in algebra can cause difficulty for some students who have problems learning algebra and tend to show less positive attitudes toward algebra. In order to engage the students to algebraic thinking then teachers should deserve interactive learning such as virtual reality. Based on some papers, the Augmented Reality has positive outcomes on learning activity. Results revealed that students who learned algebra using Augmented Reality showed significantly higher mean scores in algebra thinking and attitudes toward algebra compared to the control group. Therefore, the authors wanted to examine the effects of an Augmented Reality (AR) for junior high school students. Furthermore, the paper also discusses the vision towards the future and opportunities for further research in Augmented Reality for educational systems.